Extracellular vesicles: new horizons in neurodegeneration - Jun Chen; Chen Tian; Xiao Xiong; Ying Yang; Jing Zhang (EBioMedicine)
Summary: Extracellular vesicles (EVs) are lipid-enclosed nanovesicles secreted by diverse cell types that orchestrate intercellular communication through cargo delivery. Their pivotal roles span from supporting the development of normal central nervous system (CNS) to contributing to the pathogenesis of neurological diseases. Particularly noteworthy is their involvement in the propagation of pathogenic proteins, such as those involved in neurodegenerative disorders, and nucleic acids, closely linking them to disease onset and progression. Moreover, EVs have emerged as promising diagnostic biomarkers for neurological disorders and as tools for disease staging, owing to their ability to traverse the blood-brain barrier and their specific, stable, and accessible properties. This review comprehensively explores the realm of CNS-derived EVs found in peripheral blood, encompassing their detection methods, transport mechanisms, and diverse roles in various neurodegenerative diseases. Furthermore, we evaluate the potentials and limitations of EVs in clinical applications and highlight prospective research directions in this rapidly evolving field.